FILIPPO GRANDI REPORTS ON ROHINGYA REFUGEE CRISIS IN BANGLADESH - DINAMIKA, SORAYA GRABIELLA (Lingual Journal of Language and Culture, 2020)
This study concerns with the use of Appraisal Theory developed by Martin & White (2005), under subsumed of engagement system domain. The engagement system deals with dialogic perspective between speakers and listeners, which is influenced by the approach of Bakhtin/ Voloshinov, called heteroglossia. Heteroglossic backdrop reveals the proposition lies behind what is stated. In this study, a verbal interaction between speaker and listener is presented in the form of press conference release. Currently serving Head Commissioner of United Nations High Commissioner for Refugees (UNHCR), Filippo Grandi, held a press conference release containing of his visiting report to the camp shelter of Rohingya refugee in Bangladesh. The press conference release is a recorded-video type one, which has approximately 27:30” in length. It is led by a moderator, reported by the Head Commissioner and joined by 6 follow-up questions. Regarding to engagement system used, the utterances are then transcribed into a transcript, thus it gains approximately 395 clauses, moreover, only the utterances spoken by the Head Commissioner taken as the engagement locution realizations. The objectives of this research fall into three: a) to find out the most predominant heteroglossic backdrop Grandi encodes; b) to recognize the values and viewpoint Grandi intends to convey in his report; and c) to identify the authorial voice Grandi uses in addressing his beliefs of the Rohingya refugee crisis to the audiences. The qualitative descriptive method is applied. It is found that contract-disclaim-counter dominates the report by accounts of 55 realizations. It implies that the facts, Grandi reports may against audiences’ expectation, yet in another clause, he describes the situation which can reform audiences’ different viewpoints toward the crisis. Keywords : Appraisal Theory, Engagement System, Rohingya Crisis, UNHCR, Filippo Grandi